Formulation and physical evaluation of lotion aide of jeruju leaf extract (Acanthus Ilicifolius L) - Sari, Esti Lia Purwita; Dianita, Puspita Septie; Pribadi, Prasojo (Borobudur Pharmacy Review, 2026)
Jeruju leaves (Acanthus Ilicifolius L.) contain secondary metabolite compounds, one of which is flavonoids as antioxidants. In this study, the use of jeruju leaf extract is formulated in lotion dosage form as an antioxidant to provide long-lasting and effective protection to the skin. Lotion is a liquid emulsion consisting of water phase and oil phase stabilized by emulgator, containing one or more active ingredients in it. This study aims to determine the effect of varying concentrations of cetyl alcohol as an emulsifier and lanolin as a thickener on jeruju leaf extract lotion preparations. The research method used is experimental with lotion formula divided into 3, namely, (F1 concentration of lanolin 1g and cetyl alcohol 3g), (F2 concentration of lanolin 2g and cetyl alcohol 2g) and (F3 concentration of lanolin 3g and cetyl alcohol 1g). Physical properties testing included organoleptical test, pH test, adhesion test, spreadability test, homogeneity test, viscosity test and ritation test. The results showed that variations in alcohol and lanolin concentrations affected organoleptical physical properties, pH, adhesion, spreadability and viscosity. The lotion preparation did not affect homogeneity and irritation. The conclusion of this study is that variations in the concentration of cetyl alcohol and lanolin affect the physical properties of lotion preparations and lotion preparations of jeruju leaf extract (Acanthus ilicifolius L.) in all formulas are in accordance with established standards and safe for use.